The credibility of 'The Link' from the perspective of modern financial theory - Hans Genberg; Cho-Hoi Hui (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2008)
Hong Kong's Linked Exchange Rate System (LERS) has been in operation for twenty-five years during which time many other fixed exchange rate systems have succumbed to shocks and/or speculative attacks. This fact alone suggests that the LERS is a robust system which enjoys a large measure of credibility in financial markets. This paper intends to investigate whether this is indeed the case, and whether it has been the case throughout its 25-year history. In particular we will use the tools of modern finance to extract information from financial asset prices about market expectations that are related to the credibility of the LERS. The main focus is on how market participants `judged' the various changes made to the LERS, such as the `seven technical measures' introduced in September 1998 and the `three refinements' made in May 2005. These changes have been characterizes as making the system less discretionary over time, and we hypothesize that they have also made it more credible as revealed in the prices of exchange rate related asset prices. We also investigate the relationship between interest rates and exchange rates in the current system in light of modern models of target-zone exchange rate systems. We will examine whether the intramarginal intervention in November 2007 changed the dynamic properties of the exchange rate as suggested by such models.
urn:nbn:de:hebis:30-70488
Keywords: 330